Penerapan Strategi Sponsorship dalam Integrated Marketing Communication: Studi pada Brand Gojek - Arsy Hafiidu Tyasepti; Indri Yunita Sari; Salwa Setyawan Nisa; Devrin Keysa Salsabilla Novia; Jauhar Wahyuni (Communicator Sphere, 2026)
This study aims to analyse the role of sponsorship within Gojek's Integrated Marketing Communication (IMC) strategy. Gojek is a technology company that provides on-demand online transportation services in Indonesia. In an increasingly competitive digital industry, companies must implement integrated, value-oriented marketing communications. In this study, sponsorship is not only recognised as a short-term promotional tool, but also as a communication strategy capable of building brand image, increasing brand awareness and strengthening long-term relationships with the community. This study employs a qualitative approach with a descriptive-analytical methodology. Data were collected through a literature review and documentation of Gojek's sponsorship practices, particularly in social and educational fields. The results demonstrate that Gojek's sponsorship is integrated with other IMC elements, including digital media, public relations, and corporate social responsibility programmes. Sponsorship significantly contributes to shaping a positive brand image, increasing brand awareness and building consumer trust and loyalty.